2020
DOI: 10.3390/cells9040868
|View full text |Cite
|
Sign up to set email alerts
|

Glycation Leads to Increased Polysialylation and Promotes the Metastatic Potential of Neuroblastoma Cells

Abstract: Neuroblastoma is the second most frequent extracranial tumor, affecting young children worldwide. One hallmark of tumors such as neuroblastomas, is the expression of polysialic acid, which interferes with adhesion and may promote invasion and metastasis. Since tumor cells use glycolysis for energy production, they thereby produce as side product methylglyoxal (MGO), which reacts with proteins to advanced glycation end products in a mechanism called glycation. Here we analyzed the expression of (poly) sialic ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 35 publications
4
6
0
Order By: Relevance
“…In our previous study, we demonstrated that glycation with MGO increases the invasion of GBM cells, resulting in a more aggressive subtype [18]. Similar results were found in meningioma and neuroblastoma, where invasion was increased after glycation [19,20]. Interestingly, glycation increased polysialylated neural cell adhesion molecule (PolySia-NCAM) in neuroblastoma cells, where PolySia-NCAM is seen as an adverse prognostic marker [19].…”
Section: Introductionsupporting
confidence: 68%
“…In our previous study, we demonstrated that glycation with MGO increases the invasion of GBM cells, resulting in a more aggressive subtype [18]. Similar results were found in meningioma and neuroblastoma, where invasion was increased after glycation [19,20]. Interestingly, glycation increased polysialylated neural cell adhesion molecule (PolySia-NCAM) in neuroblastoma cells, where PolySia-NCAM is seen as an adverse prognostic marker [19].…”
Section: Introductionsupporting
confidence: 68%
“…The bifunctional effects of SLs in maintaining a proper balance between the neural system health and control of hypersalivation for the life process may play a crucial role. Such balance could avoid the formation of the excessed polySia chains, and thus may block tumor metastasis of cancer patients [59]. As Toman's Law states: "Enough of Anything will Inhibit Anything" [60].…”
Section: Discussionmentioning
confidence: 99%
“…Polysialic acid is an α-2,8-glycosidically linked polymer of Sia, usually expressed as N -glycans on neural cell adhesion molecule 1 (NCAM1) ( 35 ). The abnormal expression of polysialic acid is associated with the occurrence of lung cancer ( 35 ), breast cancer ( 36 ), and neuroblastoma ( 37 ), and is associated with poor prognosis ( 38 ). The increased level of sialylation also involves overexpression of gangliosides ( 39 42 ).…”
Section: Aberrant Glycosylation In Tumorsmentioning
confidence: 99%